The Role of Artificial Intelligence in Revolutionizing Financial Services: Opportunities and Challenges - Aisha Al-Obaidi; Tariq Al-Samarrai; Layla Al-Fadhli (Proceeding of The International Conference on Economics and Business, 2024)
Artificial intelligence (AI) is transforming the financial services industry by enhancing decision-making, risk management, and customer engagement. This study explores the adoption of AI technologies in banking, investment management, and insurance. It also addresses ethical and regulatory challenges, providing a roadmap for sustainable AI integration in the financial sector.